Effect of nitrogen fertilization on osmotic adjustment in maize and sorghum - Bataglia, Ondino Cleante; Quaggio, José Antonio; Brunini, Orivaldo; Ciarelli, Deborah Maria (Pesquisa Agropecuaria Brasileira, 2014)
To study the effect of nitrogen fertilization on osmotic adjustment, two pot experiments were conducted in a greenhouse, one with irrigated maize at two N levels. The second experiment had maize and sorghum at two N levels with and without water stress. Saturated leaves of N fertilized irrigated maize had osmotic potentials about 0.1MPa lower than N deficient leaves. There was a significant correlation between N and soluble sugar contents in the leaves. Independently of the water regime, the osmotic potential of unsaturated leaves of maize was about 0.2MPa lower for N sufficient plants than for N deficient. For sorghum, the difference in the osmotic potential was small in function of N supply, but it was about 0.1MPa lower for water stressed plants, as compared to irrigated plants. For both crops N fertilization increased the transpiration rates per unit leaf area, decreased the leaf diffusive resistance to water vapour and increased leaf N and solutes. Under moderated water stress, plants well supplied with N, specially maize, showed better osmotic adjustment by accumulation of N compounds and other assimilates. By this process they can use more efficiently the available soil water than N deficient plants.